Antioxidant activity, phenolic content, and flavonoid content of genus Hedychium (Hedychieae, Zingiberaceae) in the Philippines - Mendez, Noe P.; Elbit, Mark Glenn D.; Villafranca-Tuba, Angie Rose; Lagunday, Noel E.; Mendez, Rainear A. (2023)
The search for potential plants with natural sources of antioxidants is continuing in response to the global need for plant-derived medicines. In the Philippines, one plant family that has recently received attention is the ginger family (Zingiberaceae) because of its ethnomedicinal potential. In this study, the ethanolic extracts of the dry-weight leaves and rhizomes of three species of Hedychium present in the Philippines, viz. Hedychium coronarium Koenig, H. flavescens Carey ex Roscoe, and H. philippinense K.Schum., were determined for the total antioxidant activity (TAA), total phenolic content (TPC), and total flavonoid content (TFC). Data revealed that the leaves of these species obtained the highest values of TAA, TPC, and TFC compared to their rhizomes. The TAA (mg AAE/g dried sample) of the leaves was highest in H. coronarium (7.16 ± 0.18), whereas the value of the rhizomes was highest in H. philippinense (4.42 ± 0.60). The TPC (mg GAE/g dried sample) of the leaves was highest in H. philippinense (1.51 ± 0.03), whereas the value of the rhizomes was highest in H. philippinense (1.30 ± 0.08). In terms of the TFC (mg QE/g dried sample), both the leaf and rhizomes extracts were highest in H. coronarium with 6.29 ± 0.01 and 0.62 ± 0.02, respectively. The data obtained in this study imply that phenolic compounds significantly contribute to the antioxidant activities of the extracts of the three species. These data also mean that the three species of Hedychium in the Philippines are potential sources of natural antioxidants.
Keywords: Ginger -- Therapeutic use; Antioxidants; Endangered plants